THE DEVELOPMENT OF CHATBOT APPLICATION ON LINE MESSAGING PLATFORM FOR CUSTOMER SERVICE IN JOGJA SEWA KAMERA - Jati, Dimas Pratama; Maarif, Muhammad Rifqi (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2018)
In recent days, customer care is one of the pivotal aspects in business environment. Quick and reliable response to any of customer question was highly correlated to customer satisfaction and obviously affect the conversion rate of any kind of products or services offered to them. Jogja Sewa Camera is a small company which the main business is to rent a camera. That company serve no less than 25 booking request and questions about the product they offered to the customer. With the limitation of operational staff, the work for responding the customer booking request and question is a bit overwhelmed. Thus, an automated mechanism was built in this research to help the company to handle the customer service. In this research, a chatbot based on Line Messaging Platform was developed for automatic customer service. This chatbot can answer any of frequent or common question and booking request from the customer.